If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + -15 = 32 Reorder the terms: -15 + y = 32 Solving -15 + y = 32 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + y = 32 + 15 Combine like terms: -15 + 15 = 0 0 + y = 32 + 15 y = 32 + 15 Combine like terms: 32 + 15 = 47 y = 47 Simplifying y = 47
| -11nk^2+5nk-6y=0 | | 2[1-3(x+2)]=-x | | 54-4x=14x+22 | | 2d-17=3d+8 | | 3(y+7)+4=43 | | 142-7x=20x+22 | | q+3q=2q-6 | | x+1=-15 | | -4r+5=-3r+9 | | 3(-8x)+8=80 | | 3z-3(1-z)=z-17 | | -8h-1=-33 | | 9(y-4)-3y=6(y-6) | | 90+4x+x=180 | | 15=-2p+27 | | -6(-x-10)=10(-x-10) | | 8x-9x=73-82 | | 0.50x+0.15(70)=48.5 | | 35+x=18 | | -7(3a+10)=0 | | 4(w+1)=6-2(1-2w) | | y-81=-12 | | -8y+12=-28 | | 61+x=5 | | 9+8x=72+8 | | 3x-2x=-3-2x | | 19=4n+7 | | 5x+3-4x=9 | | 73-6x=30x+17 | | X-.28x=463.32 | | 2-4y=1-5y | | 3x+(2x+4)=5(x+1)+3 |